Sample size calculation in medical studies - Pourhoseingholi, Mohamad Amin; Vahedi, Mohsen; Rahimzadeh, Mitra (Gastroenterology and hepatology from bed to bench, 2013)
Optimum sample size is an essential component of any research. The main purpose of the sample size calculation is to determine the number of samples needed to detect significant changes in clinical parameters, treatment effects or associations after data gathering. It is not uncommon for studies to be underpowered and thereby fail to detect the existing treatment effects due to inadequate sample size. In this paper, we explain briefly the basic principles of sample size calculations in medical studies.